RELEVANSI ALIRAN IDEALISME DALAM PENGUATAN PENDIDIKAN KARAKTER PADA PEMBELAJARAN BERBASIS TEKNOLOGI DIGITAL - Ni'ma uqbalkuroma; Fika Safnatunnajah; Rizkiyya Ramadhani; Muhlisin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The massive development of digital technology in the last two decades has fundamentally altered how humans learn, interact, and shape their identities. Character education now faces unprecedented pressures as moral values once transmitted face-to-face must compete with unfiltered digital content. Despite abundant studies on digital learning, limited research specifically examines idealism as a philosophical foundation for character education in digital contexts. This study aims to: (1) describe the concept of idealism in education, (2) analyze the characteristics of technology-based learning, and (3) examine the relevance of idealism to character education in the digital era. Using a Systematic Literature Review (SLR) method applied to 24 relevant academic articles from the period 2020–2025, this study selected sources from Google Scholar, ERIC, and Portal Garuda databases using inclusion and exclusion criteria involving keywords such as